Development of Haematobia irritans in bovine faecal masses maintained under laboratory conditions - Barros, Antonio Thadeu Medeiros de (Pesquisa Agropecuaria Brasileira, 2002)
This study investigated the developmental time of the horn fly (Haematobia irritans L., Diptera: Muscidae) in bovine manure. Monthly, from May 1992 to April 1993, two dung pats were collected 48 hours after dropping in the field, and brought to the Laboratory of Entomology, in Corumbá, MS, Brazil, for insect daily collections during 30 days. Emergency of H. irritans (n=171) was observed in 79.2% of the pats, ranging from 0 to 29 flies/pat (7.1 average). The period until fly emergency (egg to adult) ranged from 9 to 17 days (monthly mean temperatures ranged 23.2 to 30.2oC), during summer/autumn and winter, respectively, suggesting that H. irritans may have about 22 generations per year.